INFLUENCE OF TEMPERATURE REGIME OF MELTING ON CHARACTERISTICS OF CAST ALIMINIUM ALLOYS - I. V. Rafalski; A. V. Arabej (Литьë и металлургия)
Temperature dependence of the melts properties of the system Al-Si with content of silicon up to 16% (masses) and influence of the temperature regime of the alloys melting in liquid phase on the structure and properties of cast metal is studied. The temperature regimes of preparation of cast aluminium alloys in liquid phase providing dispersible phases at crystallizing and increase of mechanical properties of cast metal are established. Modification of form, sizes and character of distribution of primary and eutectic phases is the result of the regime of the temperature processing of alloy in liquid state. The formalized model of evolutions of the metal system condition is offered.